Surgical Complications of Bariatric Surgery among Patients with Rheumatic Diseases - Mohsen Soori; Seyed Hadi Mirhashemi; Fariborz Rashnoo; Gholamhosein Faghih; Fatemeh Ehrahimi; Amir Zamani; Azadeh Hakakzadeh (Babol University of Medical Sciences, 2024)
Background: Obesity is one the most prevalent diseases all around the world. Some studies have shown a relationship between obesity and the worsening of rheumatic disorders. Higher rates of surgical complications might also be seen among these patients. Methods: This retrospective-descriptive study was performed on 25 patients with rheumatic disease referred to Loghman Hakim Hospital (Tehran- Iran) and candidates for bariatric surgery (laparoscopic Roux-en-Y gastric and laparoscopic sleeve gastrectomy) from 2018 to 2020. Duration of hospitalization after surgery and history of post-operation surgical and rheumatic complications were assessed. Patients were followed through 6 months after surgery. Results: The age (Mean±SD) of recruited patients was (38.4 ±10.0) years. The mean body mass index was 45.54 kg/m2 with the minimum and maximum values of 37.5 kg/m2 and 56.5 kg/m2. Among them, the prevalence of rheumatic disorders was rheumatoid arthritis 32%, psoriasis 28%, gout 16%, lupus erythematosus 8%, and other rheumatologic disorders 16%, respectively. One patient had a surgical complication that was a port site infection. One patient had a relapse of gout and other patients had remission and also, their therapeutic drugs were discontinued or reduced. Conclusion: Patients with rheumatic disorders revealed no higher surgical complication rate after bariatric surgery, and bariatric surgery helped disease remission among these patients.